Synthesis of both enantiomers of 1, 2, 3, 4-tetrahydroisoquinoline derivative IPPAM-1 and enantio-dependency of its positive allosteric modulation of prostacyclin receptor. Issue 11 (1st June 2017) - Yamamoto, Kohki; Suzuki, Toshifumi; Imamura, Riyo; Nagano, Tetsuo; Okabe, Takayoshi; Miyachi, Hiroyuki
Graphical abstract: Abstract: We present a practical synthesis of both enantiomers of 1, 2, 3, 4-tetrahydroisoquinoline derivative IPPAM-1 (1 ), which is a positive allosteric modulator (PAM) of prostacyclin receptor (IP) and a candidate for treatment of pulmonary arterial hypertension without the side effects caused by IP agonists. Assay of cAMP production by CHO-K1 cells stably expressing human IP clearly demonstrated that the IPPAM activity resides exclusively on the R-form of1 .